Preponderance of Deceit: Interpersonal Deception Theory in Parliamentary Style Debate - Bryant, Kevin Lynn (My University, 2014)
"This thesis considers whether or not an interpersonal framework is an appropriate lens to analyze collegiate level National Parliamentary Style Debate. NPDA, called Parli for short, is perhaps the largest style of debate in the United States of America. Interpersonal deception theory (IDT) was created to parse out the difference between noninteractive deception and interactive deception. This theory found in interactive context that deception was being used from three distinct vantage points. Those three types of deception were falsification, equivocation and concealment. Based on experience and literature several hypotheses are developed to test the saturation level of deceit found from both the debaters’ own self-reports and the debaters’ perception of their opponents. Several hypotheses found support for the notion that debaters believe that their opponents are being dishonest and so to do they question their own veracity levels. For instance, the debaters reported that concealment was the most utilized form of deception while falsification was the least used form of deceit. A discussion inquires about these relationships between the debaters, as well as, ethical implications and points to areas of future research. My findings show that parli debat is amenable to study with the interpersonal framework set out by IDT and should validate that debaters relationships influence their uses of deception."
Chapter 1: Introduction - 1 Growth Rate, History and Size -1 Gender Dominance -4 Educational Impacts of Deception - 6 Ethics - 8 Chapter 2: Literature Review - 10 Interpersonal Deception Theory - 10 Definitions -11 Criticisms - 14 Assumptions - 17 Propositions - 18 1 and 2 - 19 Research Question 1 - 20 3 and 4 - 20 Hypothesis 1a and 1b - 21 Hypothesis 2a and 2b - 22 5 and 6 - 22 Hypothesis 3a and 3b - 24 Hypothesis 4a and 4 b - 25 Hypothesis 5... -27 7, 8, 9 and 10.. -27 11, 12, 13 and 14 - 28 15, 16, 17 and 18 - 30 Hypothesis 6 - 33 19, 20 and 21. -33 Other IDT Literature - 34 Hypothesis 7a and 7b - 38 Summary with RQ and Hypotheses - 39 Chapter 3: Methodology - 41 Participants - 41 Procedures - -42 Data Collection - -42 IRB/Ethical Considerations - 43 Credibility - -44 M easure - 44 Construct Validity -47 Research Design. -47 Design Chosen - 47 Design Not Chosen -48 Chapter 4: Results - 51 RQ1 - 51 Hypothesis 1a and 1b - 51 Hypothesis 2a and 2b - 52 Hypothesis 3a and 3b - 55 Hypothesis 4a and 4 b - 56 Hypothesis 5 -57 Hypothesis 6 -58 Hypothesis 7a and 7b - 58 Chapter 5: Summary - 61 Discussion - 61 Limitations and Future Research -71 Conclusion -74 Works Cited - -75 Appendix A: Propositions of Interpersonal Deception Theory - 88 Appendix B: Survey Questionnaire. -90
Keywords: Interpersonal Deception Theory; IDT; Parliamentary Debate; NPDA; IPDA; Parli Debate